Projecting the Shortages and Surpluses of General Practitioners in Iran - mahdi shahraki; simin ghaderi (Shahid Sadoughi University of Medical Sciences, 2021)
Introduction: Due to the necessity of careful planning in the human capital of health and the effect of imbalance of general physician supply on economy and health status, this study aimed to estimate general practitionerschr('39') (GPs) demand and predict general practitioners' shortage and surplus in Iran. Method: This study was an analytical and applied study conducted at the national level for Iran in 2019 using ARIMA (5,1,1) method for projecting supply and Vector Error Correction (VEC) models for projecting demand with Gross Domestic Product (GDP), out-of-pocket, aging and hospital beds variables. Data were annual time series from 1991 to 2017, extracted from the statistical yearbooks issued by the Statistical Center of Iran and the World Bank database. The required models and tests were estimated by Eviews 10 software at a 0.05 significance level. Results: The general practitioners' elasticity to GDP, aging, and out-of-pocket were 0.33, 1.77, and -0.81, respectively. GDP per capita (0.11), aging (0.14), and the number of hospital beds (0.0007) had a positive impact, and out-of-pocket payments (-0.0001) had a negative impact on demand for GPs in Iran. Also, from 2018 to 2030, the mean GPs demand (0.23) was higher than the mean supply (0.20), and there was a shortage of GPs in these years (0.03). Conclusion: Iran is facing a shortage of GPs by 2030. Therefore, there are suggested policies for increasing the admissions capacity at medical universities, maintaining and preventing the migration of physicians with appropriate incentives, establishing rules, and providing job satisfaction for physicians.